Desempleo y su repercusión en el estado emocional de una mujer de 41 años en el cantón Babahoyo - Torres García, Reynaldo Joseph (2022)
This research work brings with it a case study, developed in the city of Babahoyo, where patient N001 is presented with a chronological age of 41 years, 7 months at the time of the psychological consultation, she states that she has anxiety problems and anxiety that feels sad and incapable most of the time, all because she became unemployed more than two years ago. The objective of this case study is to determine the influence of unemployment and its impact on the emotional state of a 41-year-old woman in Babahoyo Canton using the cognitive behavioral approach, through psychodiagnostic strategies. The problem to be investigated is how does unemployment affect the emotional state of a 41-year-old woman in the Babahoyo Canton? To carry out this case study, the qualitative methodology was obtained; Likewise, the methods that were used were: the case study, the psychometric method, the clinical, descriptive and bibliographic method. Techniques such as clinical interview, direct observation, psychometric tests will also be applied. Based on the results obtained, it was diagnosed according to DSMV 300.4 (F34.1). Persistent depressive disorder (dysthymia), in partial remission, with late onset, With pure dysthymic syndrome. Once unemployment and its influence on the emotional state of a 41-year-old woman from the Babahoyo canton were investigated, it can be affirmed that unemployment affects people on a psychological level, descending from their emotional state.